Agrippina - Händel, Georg Friedrich 1685-1759 (Erato, 2020)
On hearing the news that her husband, the Emperor Claudius, has been killed in a storm at sea, Agrippina plots to secure the throne for Nero, her son by a previous marriage
Libretto by Vincenzo Grimani
An opera in three parts
Programme notes by David Vickers
Interpreten: Joyce DiDonato (Agrippina), Franco Fagioli (Nerone), Elsa Benoit (Poppea), Luca Pisaroni (Claudio), Jakub Józef Orliński (Ottone), Biagio Pizzuti (Lesbo), Carlo Vistoli, (Narcisco), Marie-Nicole Lemieux (Giunone); Il Pomo d'Oro; Maxim Emelyanychev
Keywords: CD